Pelaksanaan discharge planning pada pasien diabetes melitus: Studi literatur - Linda Yulia; Tuti Pahria; Sandra Pebrianti (Holistik Jurnal Kesehatan, 2020)
Discharge planning from hospital to home among patients with diabetes mellitus: A literature studyBackground: Several studies have stated that patients with diabetes mellitus who do not get proper management when discharge after hospitalization are very at risk to readmission because of complications. Properly discharge planning programme is very essentials to reduce the number of readmission and following by controlled on patient's conditions. However, the fruitfulness level of discharge planning program in each hospital was different. planning in DM patients is still not optimal and does not explain in detail the discharge planning stages.  Purpose: To determine several studies of discharge planning programme among patients with diabetes mellitus in several hospitalMethod: Literature study method with narrative review approach. Search for articles using databases by Science Direct, Pubmed and Google Scholar by entering keywords "discharge planning or return planning, Stages or steps, Diabetes or glycemic." From the search results, there were 13,743 articles that matched the keywords, then an examination carried out based on inclusion criteria (published year 2011-2020, articles in Indonesian and English, using the retrospect cohort method, RCT, and Quasi Experiment, full-text articles, discuss discharge planning stages) and exclusion criteria (articles on systematic reviews, proceedings, editorials and books). An examination carried out based on the title, sample, research method, and getting 10 articles.Results: Analyzing result of 10 articles found that the discharge planning stage was the first stage starting from the time when admitting to hospital by conducting an assessment, diagnosis, planning, implementation and evaluation. The second stage was for the patient treated by providing education and training. Providing education included information about disease, signs and symptoms of disease, things that must avoid from experienced health problems and complications, and information about health service sources in the community. While training included the use of drugs, insulin, diet, physical activity, management of hypo and hyperglycemia, foot care, and blood glucose control. The third stage was after the patient discharged from the hospital by following up in form of telephone counseling and visits to the patient's home. The result of this literature study can be used as learning material for further research and material in providing nursing care. Keywords: Discharge planning; Hospital; Patients; Diabetes mellitus; Literature studyPendahuluan: Pasien DM yang tidak mendapatkan penatalaksanaan yang tepat sangat beresiko mengalami berbagai komplikasi. Beberapa penelitian menyebutkan pasien DM cenderung kembali menjalani rawat ulang setelah pulang dari rumah sakit akibat dari komplikasi. Discharge planning terbukti dapat mengurangi jumlah kunjungan ulang ke rumah sakit dengan keluhan yang sama dan bahkan dapat mengurangi tingkat komplikasi. Namun, untuk saat ini, pelaksanaan discharge planning pada pasien DM masih kurang optimal dan tidak secara rinci menjelaskan tentang tahapan discharge planning.Tujuan: Untuk mengetahui tahapan dalam pemberian discharge planning pada pasien diabetes melitus.Metode: Penelitian ini menggunakan metode studi literatur dengan pendekatan narrative review. Pencarian artikel menggunakan database yaitu Science Direct, Pubmed dan Google Scholar dengan memasukkan kata kunci yaitu “discharge planning or perencanaan pulang, Stages or tahapan, Diabetes or glycemic. Dari hasil pencarian ditemukan sebanyak 13,743 artikel yang sesuai dengan kata kunci, kemudian dilakukan pemeriksaan berdasarkan kriteria inklusi (terbit tahun 2011-2020, artikel dalam Bahasa Indonesia dan Bahasa Inggris, menggunakan metode kohort retrospekti, RCT, dan Quasi Experiment, artikel tersedia full text, membahas tahapan discharge planning) serta kriteria eksklusi (Artikel systematic review, proceeding, editorial dan buku). Selanjutnya dilakukan pemeriksaan berdasarkan judul, sampel, metode penelitian, dan isi sehingga didapatkan 10 artikel.Hasil: Dari 10 artikel ditemukan tahapan discharge planning tahap pertama dimulai sejak pasien masuk ke rumah sakit dengan melakukan pengkajian, diagnosa, perencanaan, implementasi, dan evaluasi. Tahap kedua selama pasien di rawat dengan memberikan pendidikan dan pelatihan. Pemberian pendidikan meliputi informasi tentang penyakit, tanda dan gejala penyakit, hal-hal yang harus dihindarkan dari gangguan kesehatan yang dialami dan komplikasi, serta informasi tentang sumber-sumber pelayanan kesehatan dimasyarakat. Sedangkan pelatihan meliputi penggunaan obat dan insulin, diet, aktivitas fisik, manajemen hipo dan hiperglikemia, perawatan kaki, dan kontrol glukosa darah. Tahap ketiga yaitu setelah pasien keluar dari rumah sakit dengan melakukan tindak lanjut berupa konseling telepon dan kunjungan ke rumah pasien. Hasil studi literatur ini dapat dijadikan sebagai bahan pembelajaran untuk penelitian selanjutnya dan bahan dalam memberikan asuhan keperawatan oleh perawat pada pasien diabetes melitus.